Magic in medieval Venice - Ryan, Michael A. (History compass, 2019)
The scholarly investigation of premodern magic has grown significantly over the past quarter of a century. Many studies have focused on learned treatises written and received by members of the intellectual elite in the medieval and early modern eras. The practice and interest in magic, however, cut across all social spectra. One aspect of this premodern interest in the occult that has been neglected in the extant scholarship has been that of the occult in the service of trickery or fraud, whose practitioners used their claims to accessing bodies of privileged knowledge to defraud others. Using the case of an anonymous alchemist, "Cristoforo di Parigi," purportedly exiled from Venice due to his alchemical practices, I trace the state of the field of studies on fraudulent magic, broadly, and in Venice, specifically. Fourteenth- and fifteenth-century Venice, furthermore, is the perfect site for such an analysis, as magic and its medieval receptivity have not been extensively studied within that specific venue during the Middle Ages.